Development of the functional connectivity of the frontoparietal mirror neuron network in preschool Children: An investigation under resting state. (December 2019) - Dai, Junqiang; Li, Chaolin; Zhai, Hongchang
Highlights: The MNS could be observed at rest. The right IPL being positively correlated to the right IFG in both the 3- and 5-year-olds. The spontaneous functional connectivity of the MNS was significantly increased in the 5-year-olds. The synchronized spontaneous neural activity across the MNS displayed a lateralization. Abstract: Previous task-related imaging studies in adults have demonstrated that there is a frontoparietal mirror neuron system (MNS) that preferentially engages in self-recognition. However, the development of the MNS during preschool (age 3–5 years) has not been thoroughly examined. In this study, we investigated the development of the MNS by examining the correlations in spontaneous fluctuations of the functional magnetic resonance imaging (fMRI) blood oxygen level-dependent (BOLD) signal in healthy, 3–5-year-old preschool children (n = 30, 15 in each group). Using a ROI-based (inferior frontal gyrus) functional connectivity analysis, we identified a right lateralized MNS during rest in both groups with a positive correlation between the inferior frontal gyrus and inferior parietal lobule. A significant increase in the functional connectivity of the MNS was observed in the older group. Our results suggest that the spontaneous functional connectivity of the MNS is shaped at as early as 3 years of age and undergoes age-related development within the preschool period.